2015
DOI: 10.1155/2015/289467
|View full text |Cite|
|
Sign up to set email alerts
|

A Review of Collagen Cross-Linking in Cornea and Sclera

Abstract: Riboflavin/UVA cross-linking is a technique introduced in the past decades for the treatment of keratoconus, keratectasia, and infectious keratitis. Its efficacy and safety have been investigated with clinical and laboratory studies since its first clinical application by Wollensak for the treatment of keratoconus. Although its complications are encountered during clinical practice, such as infection inducing risk, minimal invasion merits a further investigation on its future application in clinical practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 108 publications
(123 reference statements)
0
27
0
Order By: Relevance
“…CXL is a rapidly emerging clinical treatment for keratoconus that stiffens the cornea and prevents or minimizes further degeneration (Wollensak et al, 2003a; Zhang et al, 2015). While CXL has been proposed as a treatment for other ocular pathologies such as keratitis (Iseli et al, 2008), its main use remains the treatment of keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…CXL is a rapidly emerging clinical treatment for keratoconus that stiffens the cornea and prevents or minimizes further degeneration (Wollensak et al, 2003a; Zhang et al, 2015). While CXL has been proposed as a treatment for other ocular pathologies such as keratitis (Iseli et al, 2008), its main use remains the treatment of keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the stiffness of sclera surrounding the optic nerve head is related to glaucoma by significantly influencing the neural tissue (Burgoyne et al , 2005; Langman et al , 2005; Pavlatos et al , 2016; Sigal et al , 2005). Keratoconus is a visual distortion created by the change in corneal rigidity, causing the cornea to bulge from its normal shape (Zhang et al , 2015; Ruberti et al , 2011). Lastly, presbyopia is the loss of the ability of the eye to change focus onto near objects; most of the previous studies investigated age-related stiffening of the crystalline lens (Charman, 2008; Weale, 2000; Glasser et al , 2001; Heys et al , 2004; Pau and Kranz, 1991; Wu et al , 2015; Yoon et al , 2013; Glasser, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…UVA activates riboflavin into a triplet which, in turn, produces reactive oxygen species (ROS). ROS reacts with collagen fibril molecules in the cornea stroma and enhances the mechanical strength of the cornea to arrest the progression of keratoconus and keratectasia (15). The present study reports a case of keratectasia occurring 12 years following LASIK, and the use of riboflavin/UVA cross-linking to arrest disease progression, and ICL to correct high refractive error.…”
Section: Introductionmentioning
confidence: 75%